2022
DOI: 10.1021/acs.langmuir.2c00005
|View full text |Cite
|
Sign up to set email alerts
|

A Coarse-Grained Model for the Mechanical Behavior of Na-Montmorillonite Clay

Abstract: Sodium montmorillonite (Na-MMT) is one of the most commonly found swelling clay minerals with diverse engineering and technological applications. The nanomechanical properties of this mineral have been extensively investigated computationally utilizing molecular dynamics (MD) simulations to portray the molecular-level changes at different environmental conditions. As the environmentally found Na-MMT clays are generally sized within hundreds of nanometers, all-atomistic (AA) MD simulations of clays within such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…33 It consists of H, O, Si, Al, Mg, and Fe atoms arranged in two tetrahedral sheets and one octahedral sheet, with space between the triple-sheet layers. 21,34 A model for the mechanical behavior of Na-Montmorillonite clay 22 along with some first-principle studies conducted previously, provide valuable insight when examining the optical, structural, and electronic properties of transition metal-doped MMT 23,24 and Kaolinite 25 clay surfaces. Understanding the atomic-scale behavior of the montmorillonite clay surface is crucial due to its chemical properties, which enable the intercalation of organic molecules such as amino acids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 It consists of H, O, Si, Al, Mg, and Fe atoms arranged in two tetrahedral sheets and one octahedral sheet, with space between the triple-sheet layers. 21,34 A model for the mechanical behavior of Na-Montmorillonite clay 22 along with some first-principle studies conducted previously, provide valuable insight when examining the optical, structural, and electronic properties of transition metal-doped MMT 23,24 and Kaolinite 25 clay surfaces. Understanding the atomic-scale behavior of the montmorillonite clay surface is crucial due to its chemical properties, which enable the intercalation of organic molecules such as amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Therefore, the use of polymer-based nanocomposites, including PCNs, represents a promising avenue for developing new materials with improved properties for tissue engineering applications. [21][22][23][24][25][26][27][28][29][30][31][32] In our study, we utilized a nanocomposite system to mimic the bone tissue environment, which consists of nano MMT clay co-doped with Fe and Mg. This clay, with the chemical formula NaSi 16 (Al 6 FeMg)O 20 (OH) 4 , exhibits negative charge states resulting from the isomorphic substitution of Al by Mg and Fe in MMT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, molecular dynamics (MD) simulations [33][34][35] have been extensively utilized to study the different physical properties of clay minerals, including MMT. [36][37][38] For instance, utilizing the Grand Canonical Monte Carlo (GCMC) method, in conjunction with MD, it was found that temperature moderately lessens the range of swelling pressure of clay with a d-spacing smaller than 16 Å. 39 In another work, using steered molecular dynamics (SMD), 40 Faisal and coworkers 37 have measured interaction energies between clays and cations during loading, enabling the evaluation of the mechanical behavior of Na-MMT tactoid under compression, tension, and shear at normal temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The atomistic model in this work is derived from MMT with a formula of Al 8 Si 16 O 40 (OH) 8 . , One of the Al atoms in the octahedral sheet is substituted with a Fe atom. The resulting Fe-MMT structures are geometry optimized under LS, IS, and HS, respectively.…”
mentioning
confidence: 99%